Representation of Raden Kamandaka in the Perspective of History and Legend in Banyumas - Ryolita, Widya Putri; Purwasito, Andrik; Abdullah, Wakit; Marwah, Sofa (Jurnal Lingua Idea, 2024)
This study examines the construction of Raden Kamandaka's representation as a historical figure and a legend. Stuart Hall's representation theory technique is applied in this descriptive qualitative study. This theory defines representation as the process of establishing meaning through language, symbols, and cultural practices. The results of the study reveal that Kamandaka is represented in two different ways. From a historical perspective, Kamandaka is shown as a real person whose existence is supported by familial descent. One of the proofs is genealogical documents owned by local cultural elites such as Budi Sasongko, which prove Kamandaka's connection to the Sundanese Galuh and Pajajaran royal lines. From a legendary perspective, Kamandaka is represented through a narrative full of symbolism, such as the transformation into Lutung Kasarung, meditation in Alas Kabunan, and a love affair with Dewi Ciptarasa. This narrative reflects local values ​​that are rich in spiritual meaning, heroism, and social relations. This study concludes that the representation of Kamandaka, both as a historical figure and a legend, results from a cultural construction that integrates facts and myths. In Stuart Hall's perspective, Kamandaka is not a fixed entity but rather a narrative product that continues to develop and is negotiated by the Banyumas community through various symbols and cultural practices. This process strengthens Kamandaka's role as a significant element of local identity, both in the context of history and collective myth.